2019
DOI: 10.1002/jcla.22942
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‐lymphocyte ratio and plasma lactate predict 28‐day mortality in patients with sepsis

Abstract: ObjectiveThe predictive potential of the neutrophil‐to‐lymphocyte ratio (NLR) and plasma lactate was investigated in regard to the prognosis of patients with sepsis.MethodsSixty‐three nonsurgical and nontrauma adult patients with sepsis admitted to the intensive care unit (ICU) from September 2016 to October 2018 were consecutively included in the study. In addition, healthy subjects were assigned to a control group. Neutrophil and lymphocyte counts were evaluated via a complete blood count. Plasma lactate, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 26 publications
7
47
0
Order By: Relevance
“…In our retrospective study, we demonstrated that the NLR, IL-6, and PCT values were significantly higher in the non-survivors than in the survivors ( P < 0.01), which was consistent with the previous studies ( 15 , 40 42 ). However, there was no significant difference in CRP levels between survivors and non-survivors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our retrospective study, we demonstrated that the NLR, IL-6, and PCT values were significantly higher in the non-survivors than in the survivors ( P < 0.01), which was consistent with the previous studies ( 15 , 40 42 ). However, there was no significant difference in CRP levels between survivors and non-survivors.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, immune-related biomarkers, such as neutrophil-to-lymphocyte ratio (NLR), C-reactive protein (CRP), procalcitonin (PCT), sTREM-1, presepsin, cytokines, and various interleukins, are increasingly being evaluated for their abilities of early recognition and to predict prognosis of sepsis ( 5 , 12 14 ). NLR has been found to serve as a convenient prognostic marker in septic patients despite numerous pieces of evidence that reported the correlation between NLR and adverse outcomes of sepsis remained controversial ( 12 , 15 ). As a sign of inflammation, NLR is derived from the absolute counts of neutrophils and absolute lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with a normal lactate level alone should not be excluded life-threatening sepsis, and with high AG levels regardless of lactate levels, have high rates of mortality and should also be considered for early, aggressive therapy [ 40 ]. However, Liu and Velissaris et al [ 41 , 42 ] clearly pointed out that plasma lactate were associated with poor outcomes in patients with sepsis and predicted mortality. INR is another crucial predictive factor in the machine learning model.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are highly glycolytic with limited mitochondrial respiration 10,11 . Lactate, a major byproduct of glycolysis, was found to be released by human neutrophils 12 and increased lactate levels are used as a marker for detecting sepsis in patients 13,14 . However, mechanistic reasoning for lactate production by BM neutrophils and its potential role during the early phase of acute inflammation remain elusive.…”
mentioning
confidence: 99%